The Effect of Celebrity Endorser Keanu Angelo in Advertising on Pantene's Brand Image - Nisa Nur Azizah Rukmana; Ira Dwi Mayangsari (Budapest International Research and Critics University, 2022)
The use of celebrity endorsers as a marketing strategy is increasingly being used by well-known brands, one of which is the Pantene brand. Currently, Pantene is at the center of the audience's attention for choosing Keanu Angelo as the star of his new advertisement, namely in the Micrales Hair Supplement Bye #Rambutcapek Hello #Rambutkecharge advertisement. The purpose of this study was to determine whether there is an influence and how much influence the celebrity endorser variable has on brand image. This study uses a quantitative approach with non-probability sampling and purposive sampling techniques so that the number of samples taken from Pantene's Instagram followers for this study is 395 respondents. The data analysis technique used is simple linear regression analysis. Where the results show that there is a significant effect between the X variable (celebrity endorser) on the Y variable (brand image). As much as 68.8% of the influence or contribution is given by the celebrity endorser variable for the brand image variable while 32.1% is influenced by other variables not examined in this study. The celebrity endorser variable with the brand image variable also has a relationship that is included in the very strong relationship category, namely 0.830.